Using Social Media to Establish Authenticity: An Analysis of a Small Dairy Farm's Use of Facebook. Issue 6 (13th May 2022) - Garner, Benjamin
Abstract: The rise of consumer social media use has corresponded with an increase in business adoption of this technology for marketing purposes. In, social media platforms like Facebook allow small businesses to communicate their brand to consumers in an easy and inexpensive way. At the same time, consumers who are bombarded with thousands of advertisements on a daily basis are increasingly looking for brands that are both authentic and reflect their personal values. This case study uses qualitative methods to examine the ways one small dairy farm uses Facebook to establish itself as an authentic local food producer. By looking at the way one farmer uses Facebook in a naïve way, we also see that this uncalculated, naive communication with consumers builds his authenticity as a farmer.